Optimalisasi Potensi Wisata di Kabupaten Tuban melalui Perencanaan Ekowisata Bersepeda - Puguh Andhi Setiawan; Kadek Wiweka; Lioe Lyly Soemarni (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Cycling ecotourism is a form of sustainable tourism that integrates environmental conservation, healthy lifestyles, and community empowerment. Tuban Regency has considerable potential for development through this concept, yet it remains underutilized. This research aims to design an ecotourism cycle planning strategy that can be implemented in Tuban Regency. This study employed an explanatory sequential mixed-method approach, combining quantitative surveys with qualitative interviews and route mapping using GPS and ArcGIS. The analysis focused on identifying tourism potential, exploring tourist motivations and preferences, and examining community perceptions. Findings indicate that tourists are primarily motivated by health, stress reduction, and social interaction, while communities generally support the development of cycling routes and related infrastructure. The study proposes five main cycling routes that connect natural and cultural attractions, complemented by infrastructure such as dedicated bike lanes, rest areas, and traffic signage. These initiatives are expected to empower local communities, enhance economic opportunities, and promote environmental sustainability. The cycle ecotourism developed in Tuban Regency has the potential to become a representative model for alternative tourism development, focusing on improving the socio-economic well-being of local communities while contributing to the preservation of the natural environment and cultural heritage. This potential can be realized if implemented through a systematic, inclusive, and sustainable strategy.